(untitled) (American Journal of Islam and Society, 1985)
Introduction Library and information servi-ces need to be attuned to the needs of the users. There has been tremendous research effort and writing on the front of user and use studies to articulate the user demands and develop a better understanding for the purpose of planning. Tobin reported 477 such studies indexed in the library literature from 1960-1973. Despite this voluminous body of research, it is felt that needs of communities and specialized groups are not addressed in the literature. Study of information needs is inherently complex, and an attempt of global formulation of user needs makes it so general that it becomes meaningless. Another important dimension of studying the information needs is the contextual perspective that totality of ’user’s life world,’ should be taken into account. Such a study centers upon the user’s experience to meet his physiological, affective, and cognitive needs. Information seeking behavior is patterned by various internal and external motivators which are embedded in the user’s social situations, cultural settings, and many more factors surrounding the complex personality of the user. The socio-cultural and physical environment of the user is the foundation to understand the individual’s knowledge structures rooted in cognitive and social psychology which stimulates information needs. The information acquiring activity of the user can be investigated through study of external and internal conditions. The external conditions pertain to material, environmental, personal, and social factors. Sovenyhazy states that these personal and surrounding conditions deserve particular attention. The user needs can be identified by studying the compounding effects of numerous variables such as age, educational level, socio-economic status, occupation, language skills, ethnic background, exposure to the environmental and cultural milieu, housing location, and many more. Such an analysis is helpful in determining the information demands of the users and the deficiencies they perceive. Study of information needs becomes more meaningful if it is confined to a specialized group of users as the homogenity of the group ensures validity of generalizations and makes their application more logical. Determination of information needs, in an articulate way, becomes imperative when an agency is planning information services for its specialized clientele. However, the needs of special groups of users and researchers like ethnic and minority groups have been given little attention by the researchers so far. Realizing this deficiency, National Commission on Libraries and Information Science organized a Conference on the Needs of Occupational, Ethnic, and Other Groups in the United States with the objective of identifying the specific needs of individual groups to fulfill their information needs in a more precise and thorough way. The conference proceedings cover a few ethnic groups but again the discussions are directed to general needs of the masses. Bourne and colleagues conducted a study on the special needs of identifiable sub-groups in the setting of American Public Library. These disparate efforts indicate the professional emphasis on conducting a thorough and scientific analysis of information use patterns and behaviors of the clientele for whom the information services are to be developed ...